Increasing benefits through economic corridor development in the Lao Peoples Democratic Republic. - Frielink, Barend (Asian Development Bank, 2018)
Special economic zones play an important role in the development of the Greater Mekong Subregion (GMS) which is home to 328 million people. The Lao Peoples Democratic Republic (Lao PDR) shares borders with the other five GMS countries. However, it is not always clear to what extent the Lao PDR has benefited from the GMS program.This study identifies opportunities for the Lao PDR to increase the benefits it derives from GMS projects, particularly economic corridors. It emphasizes that regional governance arrangements can never be a substitute for national governance arrangements. Instead, national policies, capacities, and implementation arrangements will determine how the Lao PDR can maximize the potential benefits from GMS projects.